An awareness net collaborative model for schizophrenia management. (1st January 2013) - Chattopadhyay, Subhagata; Daneshgar, Farhad
Studies have shown that obstetrical complications during one's birth play significant roles in the development of schizophrenia in one's lifetime especially in males. Hence, schizophrenia needs careful management practice from one's birth. This paper argues that schizophrenia needs to be treated as a collaborative process and as a result, the 'awareness' and 'knowledge-sharing' capability of various roles involved in the management process need to be addressed explicitly. This paper proposes high-level specification of a novel methodology for identifying and evaluating the level of awareness required by these roles for 'at risk' schizophrenics throughout their lives. The authors have both applied and validated a collaborative management approach and an associated analytical tool called the Awareness Information Net (AIN) model to assist in maintaining awareness capabilities among various roles involved in the management of schizophrenics. The ultimate goal of the current study is to develop conceptual foundation for an automated workflow management system for a collaborative management process for schizophrenia.